Antisporulant activity of ergosterol biosynthesis-inhibiting fungicides in the management of apple scab, Venturia inaequalis - and R. MALHOTRA, V.S. THAKUR, G.K. GUPTA (Indian Phytopathology, 2002)
Subsequent post-symptom eradicative sprays of myclobutanil at 0.075% during the entire period of 12 days was found to reduce conidial production on sporulating lesions and followed by venturol (dodine 0.1%), prochloraz (prochloraz 0.075%), fenarimol (rubigan 0.04%) and bitertanol (baycor 0.1%) on artificially inoculated plants. This activity of myclobutanil, bitertanol and venturol was further proved effective on established scab lesions in the orchard. Keeping in view, the practical utility of eradicative sprays on the reduction of primary scab inoculum for the subsequent year, single application of a registered fungicide bitertanol at 3.0 kg/ha was, therefore, recommended for commercial sprays since 1990 to the apple orchards in Himachal Pradesh.